At 50, Janzen–Connell Has Come of Age. (7th October 2020) - Terborgh, John
Abstract: Fifty years ago, Janzen (1970) and Connell (1971) independently published a revolutionary idea to explain the hyperdiverse tree communities of the tropics. The essential observations were that seedfall is concentrated in the vicinity of fruiting trees, whereas saplings recruit at a distance from reproductive conspecifics. These observations were encapsulated in a simple focal-tree model constructed of intersecting curves for seedfall and escape from host-specific enemies postulated to attack propagules (seeds and seedlings) in the vicinity of reproductive conspecifics. In conflict with the thinking of the times, the mechanism operates from the top down rather than from the bottom up. A deterrent to broad acceptance has been the giant intuitive leap required to generalize the focal tree model to an entire forest community. Recent theoretical and empirical results have succeeded in bridging the gap between the focal tree model and its community-level implications. With these new findings, Janzen–Connell has come of age.